Bio-intensive management of borer pests for sustainable vegetable production - Rai, A. B.; Kodandaram, M. H.; Halder, Jaydeep; Singh, B. (Indian Horticulture, 2019)
Insect-borers are major constraints in sustainable vegetable production. The extent of losses by borers accounts to 17-99% in different vegetable crops. Biointensive pest management (BIPM) technologies incorporating cultural methods, sex pheromone, biopesticides, bioagents and newer molecules are highly effective, economically viable and environmental-friendly for the management of borer pests in vegetables.